2021
DOI: 10.18596/jotcsa.785109
|View full text |Cite
|
Sign up to set email alerts
|

Can soybean lipoxygenases be real models for mammalian lipoxygenases? A bioinformatics approach

Abstract: Soybean lipoxygenase-1 is one of well-studied enzymes because it is considered as a model enzyme for mammalian lipoxygenases. In general, the soybean lipoxygenase-1 is used in the test of inhibitory activities of various compounds. The present study provides a bioinformatics approach for comparison of various lipoxygenases in the databases. Their various physical and chemical parameters such as molecular weight, theoretical pI, amino acid composition, aliphatic index, and grand average of hydropathicity and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Positive control or reference compounds such as nordihydroguaiaretic acid [19], diclofenac sodium [17], and ascorbic acid [39] were used in several studies. Nevertheless, bioinformatic analysis by Cengiz Şahin and Cavas [53] suggested that soybean LOXs are not a suitable model for human LOXs due to significant sequence-based differences. In concurrence with this, Muñoz-Ramírez and coworkers [54] found that although catechols extracted from Lithraea caustica inhibited both soybean 15-LOX and human 5-LOX, the catechols were more selective against the human LOX.…”
Section: Raw Materials Referencementioning
confidence: 99%
“…Positive control or reference compounds such as nordihydroguaiaretic acid [19], diclofenac sodium [17], and ascorbic acid [39] were used in several studies. Nevertheless, bioinformatic analysis by Cengiz Şahin and Cavas [53] suggested that soybean LOXs are not a suitable model for human LOXs due to significant sequence-based differences. In concurrence with this, Muñoz-Ramírez and coworkers [54] found that although catechols extracted from Lithraea caustica inhibited both soybean 15-LOX and human 5-LOX, the catechols were more selective against the human LOX.…”
Section: Raw Materials Referencementioning
confidence: 99%
“…Positive control or reference compounds such as nordihydroguaiaretic acid [19], diclofenac sodium [17], and ascorbic acid [39] were used in several studies. Nevertheless, bioinformatic analysis by Cengiz Şahin and Cavas [53] suggested that soybean LOXs are not a suitable model for human LOXs due to significant sequence-based differences. In concurrence with this, Muñoz-Ramírez, et al [54] found that although catechols extracted from Lithraea caustica inhibited both soybean 15-LOX and human 5-LOX, the catechols were more selective against the human LOX.…”
Section: Raw Materials Reference Pepsin and Pancreatinmentioning
confidence: 99%